(untitled) (Південний архів (історичні науки), 2025)
The aim of the study is to analyze, based primarily on a periodical publication, the preconditions and consequences of the declaration of the Odesa County as famine-stricken in January 1922. Based on general scientific methods, such as analysis and synthesis, as well as the historical method, the main directions of activity of the local Odesa authorities are determined – specifically, the Odesa County Commission for Assistance to the Starving, who suffered from crop failure – regarding the organization of aid to the starving population of the Volga region. It is revealed that the declaration of the Odesa County as famine-stricken did not lead to the provision of actual food aid to that part of the region’s population that needed it. Research results: the activity of the county commission is analyzed, which primarily consisted in preparing and sending food trains to the Volga region. Such a train was sent even when, on January 14, 1922, the county had already been declared famine-stricken. In total, by February 1, 1922, 58 wagons of grain were sent from the Odesa County to the Volga region. This was despite the fact that cases of starvation deaths had already begun to be recorded in November 1921, and such cases increased in the following months. For instance, in January 1922, 70,000 people were starving in Odesa County. Conclusions: When the drought created a real threat of famine, the local authorities in Odesa tried to take measures to mitigate the effects of the drought and prevent famine, but the efforts did not go beyond good intentions. Later, the authorities, following the instructions of the Bolshevik government of Russia, began to organize aid for the starving in the Volga region. This goal defined the activities of the Odesa County Commission for Assistance to the Starving, who suffered from crop failure. Under the commission’s leadership, 58 wagons of grain were sent to the Volga region. These wagons were sent even when cases of starvation deaths had already been recorded and certain counties of the county were recognized as famine-stricken. The fact of declaring counties or the county as famine-stricken did not mean the immediate and actual provision of aid to the starving due to the lack of sufficient resources. Nevertheless, some aid began to be provided –for instance, free meals started to be distributed. Another form of assistance for Odesa residents was the distribution of food by the charitable committee "Joint", which supplied food shipments from the United States.